Internationalization Patterns of Multilatinas (2019)
The following paper addresses an issue that has been gaining importance in today’s world: Multilatinas. Those are companies that have emerged from Latin American developing economies and that during the last decades have been growing really fast in the national and the international field. Through this paper we studied the importance of Multilatinas in the region, their common characteristics and their internationalization processes in order to identify if there is a common pattern in their international moves. Actually, the economic openness of Latin America in the 90s left two options for enterprises: to modernize or to disappear. Therefore, Multilatinas represent the survivors from this phenomenon that flourished in adverse conditions through a process of “learning-by-doing”.